Development of a Geographic Information System for Archiving Flood Prevention Recommendation Letters Using The Prototype Method - Giovan Alshary; Feri Candra (P3M Politeknik Negeri Bengkalis, 2024)
The Public Works and Spatial Planning Office (PUPR) of Pekanbaru City, particularly the Water Resources Division (SDA), faces challenges in flood management due to a lack of effective data management systems related to housing, flood points, and river basins. The absence of adequate Geographic Information Systems (GIS) and digital archiving makes flood management suboptimal, potentially worsening its impacts on the ground. This study aims to develop a GIS and digital archiving system to support the SDA Division in mitigating flood risk in Pekanbaru City. The development method used is a prototype, employing MySQL database technology, PHP programming language, Laravel framework to facilitate code writing, Bootstrap for visual layout, and Leaflet JavaScript Library for mapping features. The results of testing using BlackBox Testing indicate a 100% success rate in the functional implementation of the system. Meanwhile, the results of the User Experience Questionnaire (UEQ) show positive evaluations in all aspects, with average scores of attractiveness (2.067), clarity (2.250), efficiency (2.200), accuracy (2.150), stimulation (2.050), and novelty (1.800), which overall received an